Governance arrangements for the Zambian information legislation - Salati, Chibwe (My University, 2017)
The purpose of this study was to investigate factors leading to problems experienced in the governance system in the management of access to information legislation in Zambia. The study aimed to answer the question what are the governance challenges for the Zambian access to information law? The literature review discussed the main concepts of this research such as transparency and accountability and also looked at Governance as the field of study that this research is based. The study was qualitative in nature used the case study research design. The data collection method utilised was interviews using the semi- structured interview schedule. The method of data analysis selected was content analysis, focusing on Elite and Policy network theories to aid the analysis of findings. Findings showed that there is a fragmented system of governance in the country, one that does not seem responsive to the needs of the people. The study identified some of the challenges to the Zambian governance system such as the lack of understanding of democracy, lack of civic education by government, and high levels of both illiteracy and poverty.
Thesis presented in partial fulfillment for the degree of Master of Management (in the field of Public Policy) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand October 2017
Keywords: Zambia.--Promotion of Access to Information Act, 2000.; Privacy, Right of--Zambia; Freedom of information--Zambia